2017
DOI: 10.21859/jne-05065
|View full text |Cite
|
Sign up to set email alerts
|

The effects of foot reflexology on the level of depression in patients under hemodialysis

Abstract: Introduction: Depression is the most common psychological problems in hemodialysis patients that may lead to decreased quality of life and increased mortality rate. The aim of this study was to investigate the effect of foot reflexology on depression in patients undergoing hemodialysis. Methods: This clinical trial conducted on 78 patients who were admitted to hemodialysis wards in Imam Ali hospital and Iran Mehr Clinic of Bojnord City. Probability convenient sampling technique was used to select the sample. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Reflexology is a popular form of complementary and alternative medicine (CAM) Although some studies show negative results [9], present research show that Reflexology is an effective medical intervention in reducing depression in patients undergoing hemodialysis [10] Reflexology was found to reduce the symptoms experienced by breast cancer patients, while at the same time increasing the functional and general health status [11]. it has been found that foot reflexology in Over Activity Bladder treatment increases quality of life, and decreases depressive symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Reflexology is a popular form of complementary and alternative medicine (CAM) Although some studies show negative results [9], present research show that Reflexology is an effective medical intervention in reducing depression in patients undergoing hemodialysis [10] Reflexology was found to reduce the symptoms experienced by breast cancer patients, while at the same time increasing the functional and general health status [11]. it has been found that foot reflexology in Over Activity Bladder treatment increases quality of life, and decreases depressive symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…For this reason reflexology massage of the foot causes physiological and local changes in the body and provides a deep state of relaxation in the mind and body. Therefore, most people report an improvement in their health and well-being (Amini et al, 2017). Generally, foot reflexology is useful in improving the quality of sleep of individuals, although no study was found on the impact of this intervention on the quality of sleep and its different levels in women to provide a more accurate analysis, but it can be said that this intervention in patients with acute conditions and those with signs and symptoms is more effective than those patients with chronic diseases and prolonged symptoms and complications.…”
Section: Discussionmentioning
confidence: 99%
“…She first cleaned the patient's foot with cotton soaked in warm water, warmed her hands so as not to irritate the patient, and used one-two cc of baby oil to facilitate the massage. She massaged the foot without applying pressure on the standard reflex points with the same duration as the intervention group [ 24 ]. Thus, this protocol lasted 30 minutes (15 minutes per foot) for 4 weeks, 3 times a week.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of studies on sexual function showed contradictory results of aerobic exercises and no effect of resistance training on patients' sexual functions [ 22 ]. The effect of reflexology was studied on factors such as the severity of fatigue [ 23 ], depression [ 24 ], restless legs syndrome [ 25 ], pain, muscle cramps [ 26 ], sleep quality [ 27 ] of the hemodialysis patients, but no study has investigated the effect of reflexology on sexual function of the hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%